2016
DOI: 10.14429/dsj.66.9618
|View full text |Cite
|
Sign up to set email alerts
|

Blast Valve Design and Related Studies : A Review

Abstract: The protective structures required for performing critical operations are vulnerable to the blast and shock loads of advanced weapons. A blast valve is an important component of such structures for ventilation during normal conditions and for protection from blast/ shock during explosion. In this paper, various aspects of blast valve design and related studies are briefly reviewed. The concept and effects of blast wave, blast impact, numerical modelling and deformation of circular plate (one of the critical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The higher amplifying ratio is observed when the front wave angle of incidence is perpendicular to surface. The value of positive impulse is the area under the pressure time-history curve 5 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher amplifying ratio is observed when the front wave angle of incidence is perpendicular to surface. The value of positive impulse is the area under the pressure time-history curve 5 .…”
Section: Methodsmentioning
confidence: 99%
“…An explosion is a sudden release of energy and can be classified as physical, nuclear or chemical, depending on the source 4,5 . This paper deals with chemical explosions, which are the result of exothermic chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It is revealed that the radial displacement of such shells is minor compared to flat structures. The same authors conducted a literature review of existing blast safety valves and related studies (Sharma et al, 2016). A classification of existing safety valves is carried out, where it is among others differentiated between remote actuated (active) and blast actuated (passive) valves.…”
Section: Introductionmentioning
confidence: 99%
“…An explosion is a sudden release of energy and gases at high pressure and temperature, which causes several effects, most of which are lethal 3,4 . This release compresses the surrounding fluid, generating a mechanical shock wave that moves in all directions with an epicenter at the origin of the detonation 3,5 .…”
Section: Introductionmentioning
confidence: 99%